Citizenship in a Connected Canada: A Research and Policy Agenda - Dubois, Elizabeth; Martin-Bariteau, Florian (Université d'Ottawa | University of Ottawa, 2020)
What does it mean to be a citizen in Canada in a digital context? What are the implications of this digital setting for citizens and policy making? Citizenship in a Connected Canada brings together scholars, activists, and policy makers to examine what a connected society means for Canada. This foundational resource offers insight on the state of citizenship in a digital context in Canada and proposes a research and policy agenda for the way forward.
● Preface — Elizabeth Dubois and Florian Martin-Bariteau ● Introduction: Citizenship in a Connected Canada — Elizabeth Dubois and Florian Martin-Bariteau ●  ● PART I: Building an Inclusive Society in a Digital Context ● 1. Decolonizing Digital Spaces — Alexander Dirksen ● 2. Telling a Different Story: Canadian Citizens and Their Democracy in the Digital Age — Adelina Petit-Vouriot and Mike Morden ● 3. Framing the Challenges of Digital Inclusion for Young Canadians — Leslie Regan Shade, Jane Bailey, Jacquelyn Burkell, Priscilla Regan, and Valerie Steeves ●  ● PART II: Building Democratic Institutions in a Digital Context ● 4. Government in the Connected Era — Kent Aitken ●  5. Data Governance: The Next Frontier of Digital Government Research and Practice — Amanda Clarke ●  6. The Conversation Canada: Not-for-Profit Journalism in a Time of Commercial Media Decline — Mary Lynn Young and Alfred Hermida ●  7. Influencing the Internet: Lobbyists and Interest Groups’ Impact on Digital Rights in Canada — Megan Beretta ●  ● PART III: Rethinking Legal Frameworks for the Digital Context ● 8. Consumers First, Digital Citizenry Second: Through the Gateway of Standard-Form Contracts — Marina Pavlović ● 9. A Human Rights-Based Approach to Data Protection in Canada — Teresa Scassa ● 10. Making Sense of the Canadian Digital Tax Debate — Michael Geist ●  11. Online Abuse, Chilling Effects, and Human Rights — Jonathon W. Penney ● Conclusion : Next Steps for a Connected Canada — Elizabeth Dubois and Florian Martin-Bariteau ● Contributors ● Index
Keywords: Citizenship; Canada; Digital Spaces; Democracy